2001
DOI: 10.1091/mbc.12.5.1257
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Initiation of S Phase, Replication Checkpoint Signaling, and Maintenance of Mitotic Chromosome Structures during S Phase by Hsk1 Kinase in the Fission Yeast

Abstract: Hsk1, Saccharomyces cerevisiae Cdc7-related kinase in Shizosaccharomyces pombe, is required for G1/S transition and its kinase activity is controlled by the regulatory subunit Dfp1/Him1. Analyses of a newly isolated temperature-sensitive mutant, hsk1-89, reveal that Hsk1 plays crucial roles in DNA replication checkpoint signaling and maintenance of proper chromatin structures during mitotic S phase through regulating the functions of Rad3 (ATM)-Cds1 and Rad21 (cohesin), respectively, in addition to expected es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 78 publications
3
133
0
Order By: Relevance
“…We previously reported hsk1-89, a temperature-sensitive allele of hsk1 ϩ encoding the fission yeast Cdc7 homologue, and showed that hsk1 ϩ function is essential for mitotic S phase (14). We noticed that the hsk1-89͞ hsk1-89 homozygous diploid cells frequently failed to complete meiosis, and most cells were arrested with one nucleus (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We previously reported hsk1-89, a temperature-sensitive allele of hsk1 ϩ encoding the fission yeast Cdc7 homologue, and showed that hsk1 ϩ function is essential for mitotic S phase (14). We noticed that the hsk1-89͞ hsk1-89 homozygous diploid cells frequently failed to complete meiosis, and most cells were arrested with one nucleus (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…We previously reported that sister chromatid cohesion during mitosis is partially impaired in hsk1-89 cells (14). It is an intriguing possibility that defective meiotic sister chromatid cohesion in hsk1-89 may lead to impaired chromatin remodeling, a prerequisite for meiotic recombination.…”
Section: Discussionmentioning
confidence: 97%
“…The accumulation of XDbf4 during maturation could indicate that the XCdc7/Dbf4 complex is required for meiosis. Alternatively, the potential involvement of XCdc7/Dbf4 in sister chromatid cohesion, origin recognition complex localization, or gene regulation, as shown in different organisms, could explain why the complex binds to chromatin in a pre-RC independent manner (12,40,42,43). Additional studies will be needed to define the role of XCdc7/Dbf4 during the early embryonic cell cycle and determine whether a zygotic version of the XCdc7/Drf1 complex is also required for initiation of DNA replication during the somatic cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Genes identified in this way are candidates for roles at replication origins S. pombe. Here, a mutation in hsk1 ϩ , which is the homolog of the S. cerevisiae CDC7 encoded serine threonine and at the replication fork and can, in principle, un-kinase, leads to a cohesion defect (Takeda et al 2001; couple the initiation of DNA replication with the establishment of sister chromatid cohesion. Bailis et al 2003).…”
Section: Discussionmentioning
confidence: 99%